How to effectively treat migraine attacks - V. A. Parfyonov (Медицинский совет, 2014)
Migraine is one of the most common causes of disability of young and middle-aged people. Many patients with migraine are not satisfied with drugs used for the treatment. Rational approach to the treatment of migraine and effective relief of migraine attacks are discussed. Medicines for the treatment of migraine attacks and their evidence-based efficacy are analyzed. The efficacy and safety in relieving migraine of Excedrin containing 250 mg acetylsalicylic acid, 250 mg paracetamol and 65 mg caffeine, are described.